PENGARUH MEDIA BUSY BOOK TERHADAP KESADARAN TUBUH (BODY AWARENESS) ANAK USIA 5-6 TAHUN DI TK SHAFA MARWAH - Amelia; Rina Syafrida; Nancy Riana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the impact of using Busy Book media on body awareness in children aged 5 to 6 years at Shafa Marwah Kindergarten. This study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The research sample consisted of 15 children selected through simple random sampling. Data collection was carried out through observation using an assessment sheet that had undergone validity and reliability testing, while data analysis included descriptive statistics, normality and hypothesis testing using the Paired Sample t-Test. The results showed that before the treatment, children's body awareness was in the